2023
DOI: 10.3389/fmicb.2023.1097148
|View full text |Cite
|
Sign up to set email alerts
|

The role of the gut microbiome and its metabolites in cerebrovascular diseases

Abstract: The gut microbiome is critically involved in maintaining normal physiological function in the host. Recent studies have revealed that alterations in the gut microbiome contribute to the development and progression of cerebrovascular disease via the microbiota-gut-brain axis (MGBA). As a broad communication network in the human body, MGBA has been demonstrated to have significant interactions with various factors, such as brain structure and function, nervous system diseases, etc. It is also believed that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 168 publications
0
4
0
Order By: Relevance
“…These data indicate that these patients had significant dysbiosis [21]. In addition, Hemorrhagic Transformation (HT) was found to correlate with serum levels of SCFA, especially butyrate, and with the inflammatory response [22].…”
Section: The Role Of Sports and Nutrition In Neurological Healthmentioning
confidence: 71%
“…These data indicate that these patients had significant dysbiosis [21]. In addition, Hemorrhagic Transformation (HT) was found to correlate with serum levels of SCFA, especially butyrate, and with the inflammatory response [22].…”
Section: The Role Of Sports and Nutrition In Neurological Healthmentioning
confidence: 71%
“…In addition to inflammation, metabolites of gut microbes may influence aneurysm rupture. Shikata et al (2019) and Xu et al (2023) found that taurine reduced the risk of aneurysm formation and rupture in mice, and taurine supplementation reversed aneurysm progression.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence has revealed a strong connection between the gut and the brain—referred to as the gut–brain axis—and the composition of the gut microbiota and their derivative OMVs have an important impact on neurological disorders [ 88 , 89 ]. It is reported that, by using mice overexpressing α-synuclein, more α-synuclein aggregates were deposited in the brains of control mice compared to those of germ-free mice, and oral administration of specific bacterial metabolites to germ-free mice enhanced neuroinflammation and motor symptoms, suggesting that the gut microbiota and their secretions in the form of OMVs transmission might be an important contributor to α-synuclein pathology and microglia activation in Parkinson’s disease [ 90 ].…”
Section: Bacterial Evsmentioning
confidence: 99%